Design Analysis of Omnidirectional Single Reflector Antennas Synthesized for a Cosecant Squared Coverage in Elevation Plane - Marcansola, I [UNESP]; Silva, L. R. G. da [UNESP]; Penchel, R. A. [UNESP]; Santos, D. P. S. [UNESP]; IEEE (Ieee, 2019)
This work explores a Geometrical Optics based procedure to design axis-symmetric single reflector antenna to offer omnidirectional coverage with an arbitrary radiation pattern in the elevation plane. The reflector surface is bodie-of-revolution generated from a shaped generatrix locally described by a set of local conic sections consecutively concatenated. To illustrate the method, a reflector surface illuminated by a TEM coaxial horn was designed to radiate a co-secant squared radiation pattern.